Effectiveness and Safety of Acupuncture for Vascular Cognitive Impairment: A Systematic Review and Meta-Analysis - Su, Xin-Tong; Sun, Ning; Zhang, Na; Wang, Li-Qiong; Zou, Xuan; Li, Jin-Ling; Yang, Jing-Wen; Shi, Guang-Xia; Liu, Cun-Zhi (Frontiers in Aging Neuroscience, 2021)
Background: Acupuncture may be a promising complementary therapy for vascular cognitive impairment (VCI) and has been extensively applied in China. This review aimed to systematically appraise the overall effectiveness and safety of acupuncture in treating VCI. Methods: Seven electro-databases (CENTRAL, PubMed, Embase, CNKI, CBM, VIP, and Wanfang) were searched for randomized clinical trials (RCTs) investigating the effects of acupuncture on VCI from inception to February 28th, 2021. Two investigators identified eligible RCTs and extracted data independently. Risk of bias within each individual trial was evaluated using the Cochrane Collaboration’s tool. Meta-analyses were conducted in RevMan software (version 5.3). The strength of evidence was rated with the online GRADEpro approach. Results: A total of 48 RCTs involving 3778 patients with VCI were included. The pooled data demonstrated that acupuncture was more beneficial for global cognitive function (MD 1.86, 95% CI 1.19 to 2.54, P < 0.01) and activities of daily living (MD -3.08, 95% CI -4.81 to -1.35, P < 0.01) compared with western medicine (WM). The favorable results were also observed when acupuncture was combined with WM (MD 2.37, 95% CI 1.6 to 3.14, P < 0.01) or usual care (MD 4.4, 95% CI 1.61 to 7.19, P = 0.002) in comparation with the corresponding control conditions. Meanwhile, the subgroup analysis did not indicate a statistical effect difference between manual acupuncture and electroacupuncture (inter-group I2 < 50% and p > 0.1) when comparing acupuncture with WM. There were no significant differences in the occurrence of adverse events between the acupuncture group and the control group (P > 0.05). The evidence certainty was low or very low owing to the poor methodological quality and considerable heterogeneity. Conclusions: This review suggests that acupuncture as one monotherapy or adjuvant therapy may play a positive role in improving cognition and daily performance for VCI patients with few side effects. Different styles may not significantly influence its effectiveness. More rigorously designed and preregistered RCTs are highly desirable to verify the therapeutic benefits and determine the optimal acupuncture paradigm. The methodological and reporting quality of future researches should be enhanced by adhering to authoritative standardized statements.